2003
DOI: 10.1148/radiol.2263011623
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Features of Primary Sclerosing Cholangitis: Patterns of Cirrhosis in Relationship to Clinical Severity of Disease

Abstract: The spectrum of MR imaging appearances of PSC is diverse and comprises distinct patterns that do not appear to correlate with severity of disease. Large regenerative nodules are a frequent finding and may help to establish the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 46 publications
5
59
1
5
Order By: Relevance
“…They were indeed observed in more than half of SC patients who had imaging findings suggestive of cirrhosis. 28 In conclusion, our data do not support the need for routine radiological evaluation of the biliary tree in adults with a diagnosis of AIH. Indeed, the prevalence of overlapping SC in these patients appears very low-below 2% in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…They were indeed observed in more than half of SC patients who had imaging findings suggestive of cirrhosis. 28 In conclusion, our data do not support the need for routine radiological evaluation of the biliary tree in adults with a diagnosis of AIH. Indeed, the prevalence of overlapping SC in these patients appears very low-below 2% in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…As to the absence of first ductules, it is important for clinical practice for two reasons: the first as a sign of fibro-obliterative deseases [18][19][20][21][22][23][24][25][26] and the second considering minimum detectable duct caliber in imaging radiologic researches [27][28][29]. From LDLT point of view it is important in evaluation of age and functional-size-mass related liver parenchyma changes for donors and recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In PSC, insufficient biliary drainage of the more peripheral aspects of the liver (rather than decreased portal venous flow) ultimately results in peripheral fibrosis and atrophy [5,6]. In addition to the morphologic changes, the scattered, irregular biliary duct dilatation that is the hallmark of PSC should allow a confident diagnosis at CT.…”
Section: Discussionmentioning
confidence: 99%
“…However, portal vein thrombus does not necessarily result in cirrhosis. Indeed, recent studies in the pathology literature have indicated that alterations in portal venous flow result in a spectrum of altered hepatic histology, ranging from large regenerative nodules to nodular regenerative hyperplasia [4][5][6]. Unfortunately, the gross macroscopic changes in hepatic contour that may occur after primary portal venous occlusion are often mistaken for cirrhosis, even though bridging fibrosis is absent at histologic evaluation.…”
Section: Introductionmentioning
confidence: 99%